Discourses of leadership changeorchanges of leadership discourse? - ILIE, Cornelia (Journal of Economic Development, Environment and People, 2017)
The present study focuses on the discursively performed leadership during periods of transition and change in the context of competition-driven organizations. It explores discourses of leadership in a diachronic perspective, scrutinising the ways in which they construct and re-construct corporate and culture-related identities. Drawing on interviews and press conferences with several CEOs of two multinational companies, Nokia (Finland) and Ericsson (Sweden), an investigation of the challenges of leadership branding was carried out in a discourse-analytical and pragma-rhetorical perspective. Particular emphasis has been placed on systematically comparing the presentations in letters to employees by the CEOs of Nokia and Ericsson. This comparative study provides evidence for the internal and external challenges underlying leadership discursive construction and re-construction aimed at ensuring a consistent interconnectedness between a company’s values and its competitive qualities.